Kedudukan dan Urgensi Tempuh Upaya Administratif dalam Pemeriksaan Dismissal Process oleh Ketua Pengadilan - Baried, Rizky Ramadhan (UI Scholars Hub, 2022)
This article analyzes administrative effort (AE) in the relation of Article 62 Law 5/1986 with Article 75 Law 30/2014 and Article 2 SCR 6/ 2018. The legal questions are: 1) How was the position and urgency taken by AE in the dismissal process examination by the chairman? 2) What is the ideal formula for examining the formal requirements of the administrative lawsuit before being examined by the panel of judges? This article aims to provide a practical explanation of these norms. It is a normative juridical type with a statute and a conceptual approach. The results are: 1) AE is a formal requirement in filing a lawsuit related to competence, so the chairman can determine that the lawsuit is not accepted; 2) The dismissal process and the preparatory examination by analogy has similarities, therefore these examinations can be combined with the condition that in filing a lawsuit, the plaintiff is required to attach evidence of having taken AE. It recommends that executive/legislature make regulations related to the procedural law for examining AE, and for the supreme court to review the norms and practices of the dismissal process and the preparatory examination in relation to formal requirements for filing a lawsuit.